POTRET KEBUTUHAN TOKOH KARMAN DALAM NOVEL KUBAH KARYA AHMAD TOHARI (KAJIAN PSIKOLOGI HUMANISTIK ABRAHAM MASLOW) - Andi Nurwana Gani; Muhammad Rapi Tang; Sultan Sultan (Universitas Negeri Makassar)
The Portrait Of The Character Needs In The Novel Of Kubah By Ahmad Tohari (The Humanistic Psychological Theory Of Abraham Maslow). This study aims to describe the needs of Karman as the main character in Ahmad Tohari's Kubah novel by using a review of Abraham Maslow's Humanistic Psychology. This research is a descriptive qualitative research. The data is in the form of text excerpts that reveal aspects of the needs of karman figures obtained from the sixth edition of Ahmad Tohari's novel Kubah. Data analysis techniques using documentation techniques. The results of this study will reveal the existence of five aspects of the needs of the karman figures as the main characters namely: (1) Physiological Needs, (2) Needs of security, (3) Needs of recognition and affection, (4) Needs of Appreciation, and (5) Needs Self-actualization.